PENGARUH METODE JARIMATIKA TERHADAP HASIL BELAJAR PERKALIAN PADA MATA PELAJARAN MATEMATIKA SISWA KELAS III SDN 209 BARU II PALANGKA - Mihra; Ma'rup; Hamdana Hadaming (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the jarimatika method on multiplication learning outcomes in mathematics among third-grade students at SDN 209 Baru II Palangka. This is an experimental study using a one-group pretest-posttest design. The population of this study consists of all third-grade students at SDN 209 Baru II Palangka. The sampling technique used was saturation sampling, with a sample size of 22 students consisting of 12 boys and 10 girls. The data collection instruments used were an observation sheet as a supporting instrument and a test sheet to measure students’ multiplication learning outcomes. The data analysis techniques in this study were descriptive data analysis and inferential data analysis. The results of the study showed that the mean score on the pretest was 59.95, while the mean score on multiplication after the use of the jarimatika method (posttest) was 91.22. Furthermore, the results of the t-test analysis showed that the calculated t-value was 9.402 and the critical t-value was 2.080; thus, the calculated t-value was greater than the critical t-value (9.402 > 2.080), which means H0 is rejected and H1 is accepted, indicating that the use of the Jarimatika method has an effect. Furthermore, the percentage of students actively participating in the learning process using the jarimatika method was 95.83%. Based on the research results above, it can be concluded that the use of the jarimatika method has an effect on the multiplication learning outcomes of third-grade students at SDN 209 Baru II Palangka.